Program Kuliah Kerja Nyata (KKN) : Kegiatan Penghijauan di Desa Deli Makmur - Andrew Rinaldi Sinulingga; M. Rexi Ikhsan Wirayuda; Annisa Mawaddah Rhimadani, Annisa M.R; Qatrunnada Resty Aulia; Annisa Bintang Maharani; Christina Oktaviani; Diva Siky Apriliani; Ilham Wirmansyah; Rudvan Andari Pasoma; Evelyn C. Sinaga (Journal of Community Engagement Research for Sustainability, 2024)
KKN is a community service activity in certain areas or educational institutions, carried out in groups, integrated between departments, coordinated at the University level. The KKN (Kuliah Kerja Nyata) activity aims to provide real field work experience in the field of forming an independent attitude and responsibility in carrying out work in the field. In addition, KKN also aims to assist the community in increasing the level of knowledge and skills so that it is expected to improve their welfare. KKN activities are divided into four stages of activity, namely debriefing, implementation of activities at the location, preparation of reports, and evaluation. The implementation of this KKN starts from July 13, 2022 until August 21, 2022 in Deli Makmur Village, Kampa District, Kampar Regency. The work program in Deli Makmur Village is a program that emphasizes community empowerment. The physical program of the Deli Makmur Village KKN group includes: Greening, Gate construction, village cleaning, gymnastics, making trash cans, and maintaining the village library. Non-physical programs carried out are the implementation of Tutoring activities, Posyandu assistances. In general, KKN activities in Deli Makmur Village went very well and smoothly. This is due to the enthusiasm of the residents of Deli Makmur Village. The implementation of these KKN programs is expected to be beneficial for all parties concerned as the application and competence of the owner.